Rokopisne Kolomonove in Zdravilske bukve s Kovka nad Hrastnikom - Orožen, Martina (Slavistična revija, 2009)
The article introduces and examines the recently discovered manuscript "Kolomonov žegen in Zdravilske bukve" by Filip Orožen. It was compiled in the dialect region of the Laško sub-dialect (Kovk, Dol, Turje) towards the end of the 19th century. The texts of the Kolomon are based on the original from the Carinthian bukovniki tradition (from 1820 or 1830), written in the variety of the Slovene literary language before the introduction of the "new forms", with a considerable share of morphophonemic elements from the local dialect. In terms of content, the texts (prayers, magic formulas and charms) almost entirely match the Colemone-Shegen by bukovniki, excerpt that Orožen's version excluded all typical dialectal features of the Rož dialect that were unfamiliar in his region. The language of Zdravilske bukve is closer to his local dialect.
Keywords: bukovništvo; Kolomonov žegn; laško narečje; ljudska verovanja; rokopisi; Slovene; Slovene dialects; slovenska narečja; slovenščina; zdravilne rastline; Zdravilske bukve